The effect of cerium dioxide nanoparticles on the viability of hippocampal neurons in Alzheimer’s disease modeling - Hanzha, Vita V.; Rozumna, Nataliia M.; Kravenska, Yevheniia V.; Spivak, Mykola Ya.; Lukyanetz, Elena A. (Frontiers in Cellular Neuroscience, 2023)
The possibilities of using nanoparticle materials based on cerium dioxide (CNPs) are exciting since they are low toxic and have specific redox, antiradical properties. It can be supposed that CNPs' biomedical use is also relevant in neurodegenerative diseases, especially Alzheimer's disease (AD). AD is known as the pathologies leading to progressive dementia in the elderly. The factor that provokes nerve cell death and cognitive impairment in AD is the pathological accumulation of beta-amyloid peptide (Aβ) in the brain tissue. In our studies, we examined the impact of Aβ 1-42 on neuronal death and evaluated the potential neuroprotective properties of CNPs during AD modeling in cell culture. Our findings show that, under AD modeling conditions, the number of necrotic neurons increased from 9.4% in the control to 42.7% when Aβ 1-42 was used. In contrast, CNPs alone showed low toxicity, with no significant increase in the number of necrotic cells compared to control conditions. We further explored the potential of CNPs as a neuroprotective agent against Aβ-induced neuronal death. We found that introducing CNPs 24 hours after Aβ 1-42 incubation or prophylactically incubating hippocampal cells with CNPs 24 hours before amyloid administration significantly reduced the percentage of necrotic cells to 17.8% and 13.3%, respectively. Our results suggest that CNPs in the cultural media can significantly reduce the number of dead hippocampal neurons in the presence of Aβ, highlighting their neuroprotective properties. These findings suggest that CNPs may hold promise for developing new treatments for AD based on their neuroprotective properties.